Influence of exposure to phosphoric and polyacrylic acids on selected microscopic and physical/chemical properties of calcium hydroxide cements - Boniek Castillo Dutra Borges; Isana Álvares Ferrei̇ra; Camila Pessoa Lopes; Renato Barbosa Soares; Isabela Dantas Torres De Araújo (Istanbul University, 2020)
Purpose: This study aimed to evaluate if the contact of calcium hydroxide cements with polyacrylic and phosphoric acids would alter selected microscopic and physical and chemical properties. Materials and Methods: Chemically activated (Hydro C and Dycal Advanced Formula II) and resin-modified photoactivated (Ultra-blend Plus) calcium hydroxide cements were examined after exposure to the following different strategies: contact with no substance (control group); rinsing with water and drying; contact with polyacrylic acid, rinsing with water, and drying; and contact with phosphoric acid, rinsing with water, and drying. Surface morphology, determined by scanning electron microscopy (SEM), water sorption and solubility, and the release of hydroxyl ions were evaluated. Results: SEM showed a greater impact of the conditioning acids on the surface of the chemically activated cements. Ultra-blend Plus obtained the highest value of sorption (516.8 μg/mm3) and solubility (381.1 μg/mm3) and Hydro C had the lowest values 251.9 μg/mm3 and 206.3 μg/mm3 respectively. Considering the release of hydroxyl ions in comparison with time, Hydro C and Ultra-blend Plus presented significant statistical difference for polyacrylic and phosphoric acid subgroups. Conclusion: Hydro C and Dycal presented intensification of surface irregularities after contact with conditioning acids. The chemically activated materials suffered a decrease in sorption and solubility. The action of the conditioning acids promotes greater increase of the release of hydroxyl ions for Hydro C and Dycal.